(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
One titrimetric and two spectrophotometric methods have been described for the determination of ofloxacin (OFX) in bulk drug and in tablets, employing N-Bromosuccinimide as an analytical reagent. The proposed methods involve the addition of a known excess of NBS to OFX in acid medium, followed by determination of unreacted NBS. In titrimetry, the unreacted NBS is determined iodometrically, and in spectrophotometry, unreacted NBS is determined by reacting with a fixed amount of either indigo carmine (Method A) or metanil yellow (Method B). In all the methods, the amount of NBS reacted corresponds to the amount of OFX. Titrimetry allows the determination of 1-8 mg of OFX and the calculations are based on a 1:5 (OFX:NBS) reaction stoichiometry. In spectrophotometry, Beer's law is obeyed in the concentration ranges 0.5-5.0 µg/mL for method A and 0.3-3.0 µg/mL for method B. The molar absorptivities are calculated to be 5.53x10(4) and 9.24x10(4) L/mol/cm for method A and method B, respectively. The methods developed were applied to the assay of OFX in tablets, and results compared statistically with those of a reference method. The accuracy and reliability of the methods were further ascertained by performing recovery tests via the standard-addition method.